Isolation and Identification of Fungi Associated with Rot of Cucumber (Cucumis sativus L.) In Jimeta, Yola North Local Government Area, Adamawa State (Asian Journal of Plant Biology, 2022)
Cucumber fruit (Cucumis sativus L.) is believed to have originated from Southern Asia and fourth most important vegetable after tomato, cabbage and onion. The objective is to isolate and identify fungi responsible for rot of cucumber (Cucumis sativus L.) in the study area. Potato dextrose agar was used as growth medium. Three fungal pathogens (Aspergillus flavus, Rhizopus stolonifer and Aspergillus brasiliensis) were identified through pathogenicity test to be causing rot of Cucumber fruit in Jimeta markets (Gwari Market, Jimeta Modern Market and Jimeta Shopping Complex Market), Yola North of Adamawa state. Isolation and identification of pathogens responsible for cucumber fruit rot in Jimeta Markets were carried out, where Rhizopus stolonifera had the highest (25-48%) frequency of occurrence while Aspergillus flavus was the least (22-38%). From the study, it is concluded that Aspergillus brasiliensis, Rhizopus stolonifer and Aspergillus flavus were found out to be the fungal pathogen that caused rot of Cucumber (Cucumis sativus L.) fruit in the study area. The vulnerability of Cucumber fruit to fungal rot is not far from the poor way and manner at which the fruits are conveyed, stored and traded in the study area. It is recommended to farmers and fruit vendors to be conveying perishable fruits in soft bags and stored in cool dry places.
Keywords: Cucumis sativus L.; Potato dextrose agar; Aspergillus flavus; Rhizopus stolonifera; Aspergillus brasiliensis